(untitled) (The International Research Journal of Management Science, 2021)
The study deals with the relationship between firm characteristics of working capital management and firm profitability in Nepal. It examines if firm performance, return on assets is related to cash conversion cycle, days’ sales outstanding, days’ inventory outstanding and current ratio. The study is based on pooled cross-sectional data of 10 non-financial firms from 2071/72 to 2075/76 of listed firms in the Nepal Stock Exchange. The study employed descriptive and causal-comparative research design to attainthe purpose of this study. The result reveals that the current ratio has a positively significant relationship with profitability and days’ sale outstanding has negatively significant relationship with the financial performance of the firm.